Methodical Manual for a Set of Transport Regulations in Railway Passenger Transport - Černá, Lenka; Zitrický, Vladislav; Abramović, Borna (LOGI - scientific journal on transport and logistics, 2020)
The European Union is the first and only region worldwide where passengers have comprehensive and integrated fundamental rights on all modes of transport. The rights are based on the principles of non-discrimination, accurate, timely and accessible information as well as prompt and adequate assistance. There is also a specific code of transport regulating conditions under which a carrier transports persons, baggage, animals and goods on the rail network. The actual creation of such transport regulations should follow from a certain methodology. Thus, the paper´s objective is to propose methodical procedures that would be related to a set of regulations in railway passenger transport. The manual proposed will respect relevant legislation, which determines minimum requirements for developing transport regulations, and obligations of carriers as well. As the code of transport is part of public proposals for concluding transport contracts of the carriage of passengers, the methodical manual will contribute to making regulations in passenger transport to be better suited to practical requirements. In general, it may be argued that the manual will ensure establishing transport regulations which will be concise, clear, comprehensible, and which, in particular, will comply with the legislation and requirements of the transport service ordering party. It should therefore contain certain points to be followed when developing transport rules.